2022
DOI: 10.1055/a-1742-2736
|View full text |Cite
|
Sign up to set email alerts
|

δ-Keto Aminoacrylonitriles and δ-Keto Aminoenones from 1-Pyrrolines, Cyanoacetylenes, and Acetylenic Ketones

Abstract: The ring-opening/functionalization of 1-pyrrolines by cyanoacetylenes or acetylenic ketones (20-80 oC, MeCN, H2O) affords δ-keto aminoacrylonitriles and δ-keto aminoenones, mostly as the Z-isomers, in up to 85% yields. The synthesis involves the C(2)-N-bond cleavage in the intermediate hemiaminal resulted from the intermediate 1,3(4)-dipolar 1-pyrroline/acetylene complexes and water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…In this work, we have attempted to extend the synthesis of δ-keto aminoenones from internal acylacetylenes and 1-pyrrolines in the presence of water (Scheme ) over acylethynylpyrroles.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have attempted to extend the synthesis of δ-keto aminoenones from internal acylacetylenes and 1-pyrrolines in the presence of water (Scheme ) over acylethynylpyrroles.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of 2-hydroxyazolidine structures 8 is considered to be an intermediate step in the reaction of pyrrolines with electron-deficient acetylenes, which proceeds with the opening of the pyrroline ring and the formation of δ-keto aminonenones according to Scheme 1. [4] The direct proton transfer from the hydroxyl group to the pyrrolidine nitrogen atom with opening of the pyrrolidine ring in the isolated molecule 8 (Figure 6) requires a high activation energy ΔG � =30.47 kcal/mol. The introduction of a water molecule into the reaction as a proton carrier does not lower the activation barrier.…”
Section: Resultsmentioning
confidence: 99%
“…[3] Recent studies have shown that electron-deficient cyanoacetylenes and acetylenic ketones, with an activated triple bond due to an electron-withdrawing substituent, can interact with 1-pyrrolines leading to the formation of δ-keto aminoenones and δ-keto aminoacrylonitriles, as shown in Scheme 1. [4] In particular, such a reaction also takes place when the Nsubstituted 2-pyrrolyl group acts as R 2 . On the contrary, in the case of N-unsubstituted acylpyrrolylacetylene, instead of the expected δ-keto aminoenones, complex structures consisting of three five-membered nitrogen-containing heterocycles are formed (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations